Knowledge and Preventive Practices Regarding Gestational Diabetes Mellitus among Pregnant Women in Enugu, Eastern Nigeria: A Cross-Sectional Study - Hope Opara (The Nursing Scope, 2026)
Background: Gestational diabetes mellitus (GDM) is a significant public health concern associated with adverse maternal and fetal outcomes. Appropriate preventive lifestyle practices and early health education are essential for reducing its occurrence and associated complications. Aim: To assess knowledge of gestational diabetes mellitus and the practice of preventive activities among pregnant women attending antenatal care at Enugu State University Teaching Hospital, Enugu. Method: A descriptive cross-sectional study was conducted among 264 pregnant women selected using simple random sampling. Data were collected using a pre-tested researcher-developed questionnaire and analysed using IBM SPSS Statistics version 20.0. Descriptive statistics, including frequencies, percentages, and mean scores, were used for data analysis. The criterion mean was set at 2.5. Findings: Overall, 64.8% of respondents demonstrated adequate knowledge of GDM. The majority, 205 (84.0%), had previously heard of GDM, although only 40.6% correctly identified impaired insulin function as a contributing factor. Respondents identified previous GDM in pregnancy (152, 62.3%) and being overweight (125, 51.2%) as important risk factors. Commonly recognised complications included fetal macrosomia (181, 74.2%), stillbirth (170, 69.7%), and progression to type 2 diabetes mellitus (156, 63.9%). Knowledge of dietary modification as a preventive measure was high (98.4%); however, knowledge of other preventive activities was generally poor (71.7%). Approximately one in ten respondents (9.8%) reported using alcohol to relieve stress during pregnancy. Regarding preventive practices, most respondents (179, 73.4%) reported practising dietary modification, whereas only 20.5% engaged in regular physical exercise and 29 (11.9%) monitored their blood glucose at home. Conclusion: Pregnant women demonstrated adequate knowledge of selected aspects of GDM, particularly dietary modification, but had limited knowledge of other preventive measures. Preventive practices, especially regular physical activity and home blood glucose monitoring, were suboptimal, highlighting the need for more comprehensive antenatal education on GDM prevention. Recommendation: Healthcare providers should strengthen antenatal health education on gestational diabetes mellitus by emphasising comprehensive preventive strategies, including healthy nutrition, regular physical activity, weight management, and early screening. Policymakers and other healthcare stakeholders should implement multifaceted interventions that improve women's awareness and preventive practices to reduce the burden of GDM and contribute to the achievement of the Sustainable Development Goals. Keywords: Gestational diabetes mellitus; Knowledge; Pregnant women; Preventive practices; Prevention; Health-promoting behaviours.